ANALISIS UNSUR FISIK DOMINAN PADA OLAHRAGA TRADISIONAL - Indra Safari (Jurnal Kependidikan, 2010)
The study is aimed at finding out the dominant physical elements in traditional sports. The traditional sports studies in the research are bentengan, hadang, egrangdan lari balok. Using the qualitative research method, the study includes physical skill elements as the object of the study. The subjects of the study are 56 Semester V PGSD students. Data are recorded by observations. Descriptive qualitative analyses are subjected to the collected data. Findings show that the bentengan game is characteristized by the following physical skill elements: aerobic and anaerobic endurances, feet endurance, and sprint speed. In hadang game, the dominant physical skill elements are: reaction speed, sprint speed, and agility. In the egrang game, the emerging dominant physical skill elements are: dynamic balance, strength endurance, and coordination.In the lari balok game, the emerging physical skills are: arm endurance, coordination, and balance. From the findings, it can be concluded that these tradional games are physical exercises that are easy and not costly and that give fun and joy